2012
DOI: 10.1097/mcg.0b013e318241b335
|View full text |Cite
|
Sign up to set email alerts
|

Dyspepsia

Abstract: Dyspepsia is the medical term for difficult digestion. It consists of various symptoms in the upper abdomen, such as fullness, discomfort, early satiation, bloating, heartburn, belching, nausea, vomiting, or pain. The prevalence of dyspepsia in the western world is approximately 20% to 25%. Dyspepsia can be divided into 2 main categories: "organic" and "functional dyspepsia" (FD). Organic causes of dyspepsia are peptic ulcer, gastroesophageal reflux disease, gastric or esophageal cancer, pancreatic or biliary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 175 publications
1
46
0
4
Order By: Relevance
“…There are two types of dyspepsia: organic and functional. The main causes of organic dyspepsia are: gastroesophageal reflux, chronic peptic ulcer disease, and malignancy [4, 5]. Among the pathogenic factors of functional dyspepsia are: genetic predisposition, Helicobacter pylori (Hp) infections, inflammation, and psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of dyspepsia: organic and functional. The main causes of organic dyspepsia are: gastroesophageal reflux, chronic peptic ulcer disease, and malignancy [4, 5]. Among the pathogenic factors of functional dyspepsia are: genetic predisposition, Helicobacter pylori (Hp) infections, inflammation, and psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data supports the theory that H. pylori eradication provides significant benefits to patients with FD [711]. The Maastricht IV Consensus Report recommends this form of treatment [8].…”
Section: Introductionmentioning
confidence: 90%
“…Data from our laboratory, however, have demonstrated that group II and group III mGluRs play discrete roles in the regulation of gastric and pancreatic functions, indicating a potential target in the treatment of other GI disorders. For example, functional dyspepsia is correlated with psychological stress, anxiety and depression [61,62] and includes symptoms such as impaired gastric accommodation reflex and antral hypomotility, which may be due to derangement of vago-vagal reflexes [63,64]. Recent data from our laboratory have demonstrated that DVC administration of the group II mGluR antagonist EGLU decreases gastric tone and either decreases or reverses the gastroinhibition induced by DVC microinjection of the prototypical antistress hypothalamic hormone oxytocin [46].…”
Section: Potential Therapeutic Uses Of Mglur Agonistsmentioning
confidence: 99%